Stabilizing Zn Metal Anodes via Cation/Anion Regulation toward High Energy Density Zn‐Ion Batteries (Adv. Energy Mater. 8/2023). Issue 8 (24th February 2023) - Zhao, Ran; Yang, Jingjing; Han, Xiaomin; Wang, Yahui; Ni, Qiao; Hu, Zhifan; Wu, Chuan; Bai, Ying
Abstract : Aqueous Zinc‐Ion Batteries In article number 2203542, Chuan Wu, Ying Bai, and co‐workers develop a unique strategy to achieve aqueous Zn metal anodes with long lifespan, deep Zn plating/stripping ability and high current tolerance. A microporous artificial layer alleviates the side reactions by repelling the sulfate groups, inducing Zn deposition with the preferred orientation and homogenizing Zn ion flux to achieve a dendrite‐free morphology.